Intertextual Links of Johann Ferdinand Kelch’s poem Lietuvininkai: Christian Gottlieb Mielcke’s Poem Pilkainis - Sidabraitė, Žavinta (Senoji Lietuvos literatūra, 2024)
Johann Ferdinand Kelch’s (Lith. Johanas Ferdinandas Kelkis, 1801–1877) poem Lietuvininkai (Prussian Lithuanians), composed in the second half of the nineteenth century, was first published in the monthly magazine Saulėteka (Sunrise, Nos 8–9, 1900), edited by Martynas Jankus (1858–1946) and printed in his print shop. It is a 472-line historical poem written in a four-line cross-rhymed iamb. The first historical poem in Lithuanian – Pilkainis by Christian Gottlieb Mielcke (Lith. Kristijonas Gottlybas Milkus, 1733–1807), printed in the early nineteenth century – inspired Johann Ferdinand Kelch to write his own historical poem Lietuvininkai. Kelch’s decision to build on and interpret his predecessor in his own way was a natural one: this was due to the issues of national and religious identity, which had become highly relevant in the socio-cultural context of mid-nineteenth-century Prussian Lithuania. The intertextuality of Lietuvininkai should not be seen as a literary method consciously chosen by the author but as a kind of unfolding of the collective subconscious. Mielcke based his poem on the rationalist model of historical development that had gained a foothold in the Age of Enlightenment. Kelch built the story of the Prussian Lithuanians on a religious narrative of history. By tracing the ancestry of the Prussian Lithuanians back to the descendants of the biblical Noah, he seemed to try to inculcate Christianity into the ancestors of the old Balts and at the same time to suppress the memories of historical injustice, which had been reawakened by the Germanisation that had intensified in the mid-nineteenth century. Mielcke’s poem became a suitable model, which, when followed, supplemented, and adjusted, made it possible to rethink the most dramatic period of the nation’s history, to strongly suggest that Christianisation of the Prussian Lithuanians was God’s intended plan, and that having won eternal salvation, one should not really regret the loss of national greatness. The Germans, who brought Christianity to Prussian Lithuania, replaced the descendants of the Lithuanians who had once come to the region. A natural civilisational change took place: some newcomers had replaced others. In his poem, Kelch abandons Mielcke’s optimistic idea of an equal partnership between the two nations. Kelch borrowed the theme, the plot, and the rhyme scheme from Mielcke and incorporated textual interpolations into his poem. The fact that he took note of, adopted, and developed the most artistic episodes of Mielcke’s otherwise artistically less strong poem shows that he had a good philological ear. Kelch’s act of re-reading and reinterpreting Mielcke’s poem is unparalleled in nineteenth-century Lithuanian literature. It is a unique artistic experiment that not only imparted additional depth (the perceptual vertical) to Kelch’s poem, but also actualised the source that inspired the creative act in the cultural memory of the nation – Christian Gottlieb Mielcke’s poem Pilkainis.